The Influence of Health Promotion on The Health Behavior of Students - Sisca Nur Rohima; Dodik Hartono; Zainal Abidin (KHD Production, 2025)
Health issues arise from human behavior in interacting with themselves and their environment. The Healthy Indonesia 2025 policy establishes three pillars: healthy behavior, a healthy environment, and equitable, high-quality healthcare services. Living in group settings, such as Islamic boarding schools, poses risks of quickly contracting various diseases, particularly skin diseases like ringworm, itching, tinea versicolor, athlete’s foot, and scabies. Transmission occurs when personal and environmental hygiene is not adequately maintained. This study aims to determine the effect of health promotion on health behavior among students at the Raudlotul Falah Islamic Boarding School in Lumajang. The research design employs a pre-experimental method with a pre-test and post-test one-group design. The sample consisted of 32 students selected using purposive sampling. Data collection was conducted using a questionnaire. The Wilcoxon statistical test was used to analyze the data. The study concluded that health promotion positively influenced students' clean and healthy living behavior at the Raudlotul Falah Islamic Boarding School. Before the intervention, all respondents (32 students, 100%) exhibited poor health behaviors. Following health promotion, 13 students (40.6%) remained in the poor health category, 17 students (53.1%) improved to a moderately healthy category, one student (3.1%) reached a healthy category, and one student (3.1%) attained a very healthy category. The impact of health promotion on clean and healthy living behaviors was statistically significant, as evidenced by the Wilcoxon test results, which showed a p-value of 0.000 (<0.05). To enhance these outcomes, implementing solutions such as increased education and counseling programs for students on the importance of healthy lifestyles is recommended. These initiatives could involve distributing educational materials, conducting health campaigns, or holding seminars using print media, games, or simulations.